Crisis Management in Education: Strategies for Resilience and Adaptation in Diverse Cultural Contexts - Johnson, Katherine Reynold (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
Crisis management in education is a critical aspect of ensuring the resilience and adaptation of educational systems, particularly in diverse cultural contexts. This article explores various strategies employed to address crises in education and examines their effectiveness across different cultural settings. Through qualitative methods, literature reviews, and library research, this study investigates how educational institutions respond to and recover from crises while considering the cultural nuances that influence these processes. In conclusion, crisis management in education requires a multifaceted approach that integrates proactive planning, resilience-building efforts, cultural sensitivity, and effective communication strategies. By adopting these strategies, educational institutions can enhance their capacity to respond to crises and promote resilience and adaptation in diverse cultural contexts. This study contributes to the literature by highlighting the importance of cultural considerations in crisis management and providing insights into best practices for ensuring the safety and well-being of students and staff in times of crisis.